Re-examining psychometric properties of fertility problem inventory: A clinic-based study from India - Ansha Patel; Binu Valsalakumari Sreekumaran Nair; Sumit Kumar Das; Pratap Kumar; Podila Satya Venkata Narasimha Sharma (Wolters Kluwer Medknow Publications, 2022)
Background: The fertility problem inventory (FPI) is one of the most widely used measures that tap the diverse psychological problems faced by infertile couples. Research on translated versions of FPI has also reflected its high clinical significance. Aim: This research aimed to explore the psychometric properties and the clinical validity of the original 46-item FPI in an Indian sample. Setting and Design: This cross-sectional study was conducted in a tertiary hospital setup of a medical college. Materials and Methods: The original FPI was translated and pilot tested. The translated FPI was taken by 205 consenting infertile patients (113 women and 92 men). The psychometric properties of FPI were thus explored. Statistical Analysis Used: Exploratory factor analysis with minimum residual method of extraction followed by oblimin rotation was performed. Perceived Stress Scale was used to establish the convergent validity of the newly developed FPI-Kannada version (FPI-K). A cut-off score for the FPI-K was obtained separately for males and females using ROC analysis in which hamilton anxiety scale was used as the gold standard. Results: Only 32 items of the original FPI had factor loadings above 0.3 and overall six factors explained these items with a cumulative percentage variation of 32%. Overall Cronbach's alpha for FPI-K was 0.671 and it had a good convergent validity. Conclusions: The new FPI-K had 6 sub-domains and the clinical utility of same is discussed.